The quality management system in the banquet service as one of the elements of innovative development of the hotel-restaurant industry - Kuzmin, Oleg; Chemakina, Oktyabrina; Kuzmin, Anton (My University, 2018)
The work is characterized by a quality management system in the banquet service as one of the elements of innovative development of the hotel-restaurant industry В роботі охарактеризовано систему управління якістю в службі банкетів, як один із елементів інноваційного розвитку готельно-ресторанним господарством
Keywords: quality management system; hotel-restaurant industry; banquet service; система управління якістю; заклади готельно-ресторанного господарства; служба банкетів; кафедра технології ресторанної і аюрведичної продукції